PROSES PENGEMBANGAN KREATIVITAS PESERTA DIDIK MELALUI KEGIATAN PEMBELAJARAN BERBASIS PENDEKATAN SAINTIFIK DI SD NEGERI CIOMAS 2 - Eha, Eha; Dewi, Ratna Sari; Pribadi, Reksa Adya (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2024)
This research aims to describe: 1) plan a learning process using a scientific approach, 2) conducting learning through a scientific approach, and 3) student creativity after participating in learning through a scientific approach. The research method applied descriptive qualitative research with interview, observation and documentation as data collection techniques. Based on the analysis, the results of this research are: 1) The teacher prepares a lesson plan (RPP) which contains complete components in implementing a scientific approach because it contains a description of the teacher's instructions asking students to carry out 5M activities. 2) the implementation of learning through a scientific approach regarding aspects of observing the surrounding environment and observing pictures on students' books, questioning activities by carrying out question and answer activities during learning activities, students trying to make handicrafts, students' reasoning activities analyzing the steps making handicrafts, and communicating activities are carried out by presenting the results of their assignments in front of the class. 3) The creativity of students of grades IV, V and VI has increased as evidenced by their ability to think critically, protect the surrounding environment by holding clean Fridays, making crafts from green beans, being able to ask questions and express opinions.